Organized Colorectal Cancer Screening Programs in Switzerland – Quo Vadis? - Bianca Albers; Reto Auer; Reto Auer; Kevin Selby; Lauren Clack; Lauren Clack (International Journal of Public Health)
ObjectivesColorectal cancer (CRC) is among the most commonly diagnosed cancers in Switzerland. Supported by a solid evidence base for CRC screening, cantons have increasingly established organized screening programs. This report summarizes and discusses the state of this program landscape using findings from the Swiss Improving Organized Colorectal Cancer Screening: An Implementation Science Study.MethodsSemi-structured interviews were conducted with clinical or administrative leads for Swiss CRC screening programs to understand key characteristics, including host organization, enrollment pathways, screening modalities, and program deliverers.ResultsEleven out of 13 existing or planned programs in 2021 participated, eight of which have been developed since 2020. All programs offer mail invitations to citizens 50–69 years old and fecal immunochemical testing, though positivity thresholds vary. Access to colonoscopy and the role of healthcare providers vary between programs.ConclusionCantonal influences on designing and implementing preventive services allow programs to adapt to local conditions. However, they also challenge opportunities for cross-program learning, efficiencies, and equity. Strengthening the infrastructure connecting programs for shared knowledge building and program improvement will be vital for sustaining Swiss organized CRC screening.